Evaluating the Diagnostic Accuracy of Multi-Detector Computed Tomography in Detecting Bone Erosion Among Pre-Treatment Patients with Oral Cavity Squamous Cell Carcinoma at a Public Hospital - Kanwal, Urooj; Kadri, Shazia; Ahmed, Mukhtiar; Shoukat, Shaista; Mahmood, Tariq (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the diagnostic accuracy of multi-detector computed tomography (MDCT) using its bone reconstruction algorithm for evaluating bony erosion in pre-treatment patients of suspected oral cavity squamous cell carcinoma as a primary diagnostic imaging tool.Study Design: Cross-Sectional Study.Place and Duration of Study: Radiology Department, Jinnah Postgraduate Medical Center, Karachi, Pakistan, from Dec 21 to May 22.Methodology: All pre-treatment patients referred for a CT scan of the face and neck with high clinical suspicion of oral cavity malignancy were included. After taking proper history, a multi-planar and multi-sequential CT scan with puffed cheek technique, taking 1-3 mm contiguous slices with reconstruction using bone and soft tissue algorithm was performed. Findings of contrast-enhanced CT (CECT) scan were compared with histopathology, which was taken as the gold standard.Results: Out of 196 patients, 139(70.9%) were males and 57(29.0%) were females in a ratio of 2:1 with mean age of 50.00+11.09 years. 134(68.3%) patients with enhancing soft tissue lesions of different subsets of the oral cavity, predominantly buccal mucosa, showed adjacent bony erosion. 62(31.5%) patients, despite having soft tissue lesions/ulcerations, were negative for overlying bone involvement. Sensitivity, Specificity, PPV, NPV, and accuracy of MDCT were 95.03%, 89.09%, 95.71%, 87.50% and 93.37 % respectively, which were correlated with histopathology. A good agreement was seen amongst imaging and pathological diagnostic tests.Conclusion: MDCT reconstructed with a bone algorithm plays an indispensable role, not only in early and prompt detection of bony invasion in oral cavity squamous cell carcinoma, but also .....